2010
DOI: 10.1017/s1368980010002156
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with exclusive breast-feeding and breast-feeding in Norway

Abstract: Objective: To identify factors associated with exclusive breast-feeding and breastfeeding during the first year of life among Norwegian infants. Design: Data on breast-feeding practices were collected by a semi-quantitative FFQ. Setting: In 2006-2007 about 3000 infants were invited to participate in a populationbased prospective cohort study in Norway. Subjects: A total of 1490 mothers/infants participated at both 6 and 12 months of age. Results: Exclusive breast-feeding at 4 months was associated with parenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
115
11
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(157 citation statements)
references
References 24 publications
19
115
11
8
Order By: Relevance
“…Women need full support of their families and government to feed their children and family appropriately. Studies also found the positive trends of optimal child feeding improvement with paternal education status (Tamiru et al, 2012;Rea et al, 1999;Tamiru et al, 2012;Law et al, 2007;Kristiansen et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Women need full support of their families and government to feed their children and family appropriately. Studies also found the positive trends of optimal child feeding improvement with paternal education status (Tamiru et al, 2012;Rea et al, 1999;Tamiru et al, 2012;Law et al, 2007;Kristiansen et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…I den tidligere studien var det imidlertid betydelig lavere deltakelse og derfor risiko for at funnet ikke var representativt for befolkningen. I vår studie var andelen som fullammet derimot høyere både seks uker og seks måneder etter fødselen, sammenliknet med tidligere norske studier (11,20) og undersøkelser fra utlandet (4,26).…”
Section: Andelen Som Ammerunclassified
“…Andre har også rapportert at det er ORIGINALARTIKKEL faerre barn med lav fødselsvekt som ammes lenge (20), til tross for at amming på kort og på lang sikt kan vaere spesielt gunstig for disse (4). Det at de fleste mødrene som røykte hadde sluttet å amme seks måneder etter fød-selen, er også i samsvar med tidligere studier (11,13). Dette indikerer at grupper med risikofaktorer som beskrevet over kan ha behov for spesiell oppfølging ved helsestasjonen.…”
Section: Sammenheng Mellom Amming Og Andre Variablerunclassified
See 1 more Smart Citation
“…Presently, Scandinavian countries have some of the highest levels of breastfeeding with, for example, recent data for Norway suggesting that 96% of infants are breastfed at birth, of which 84% are exclusively breastfed. 75 In comparison to these high levels, many developed countries have much lower rates of breastfeeding, with recent Irish data suggesting that rates of exclusive breastfeeding currently stand at just 47% at hospital discharge and drop to between 6.5 and 9.4% of women partially breastfeeding during the first 6 months of the infant's life. 76 In the USA, the 2007 National Immunization Survey found that at 3 months of age, just 33% of infants were exclusively breastfed, and that this level falls further at 6 mo to just 13% being exclusively breastfed.…”
Section: Effect Of Early Feeding Regimementioning
confidence: 99%